EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) YANG DIMODIFIKASI DENGAN ASSESSMENT FOR LEARNING (AFL) PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS XI SMK TEKNIK DI KABUPATEN MADIUN - Suryanto, Suryanto; Usodo, Budi; Mardiyana, Mardiyana (Journal of Mathematics and Mathematics Education, 2017)
Abstract: The objective of this research was to investigate the effect of learning models on the learning achievement in Mathematics viewed from creativity of the student. The learning models compared were Teams Games Tournaments (TGT) The Modified By Assessment For Learning (AfL), Teams Games Tournaments (TGT) an direct model. This research is a quasi-experimental research with a 3x3 factorial design. The population of this research is all class 11th student of Vocational High School in Madiun. Sampling was done by stratified cluster random sampling of the sample totaled 266 students, with details of 87 students in the experimental class of 90 students in two experimental classes and 89 students in the control class. The instruments used to collect data were mathematics achievement test and test creativity in learning. The technique of analyzing the data was two-ways ANOVA with unequal cells. The results of research showed that: (1) The model of cooperative learning TGT modified AfL provides mathematics learning achievement better than cooperative learning model TGT and direct learning. TGT cooperative learning model provides mathematics learning achievement as well as direct learning model; (2) Students who have a high learning creativity gives better mathematics learning achievement than students who have studied creativity medium and low. Students who have studied creativity is giving mathematics learning achievement as well as students with low learning creativity; (3) For each learning model show that, the prestige mathematics students with high creativity learning are better than the student who have medium or low, and students who have the creativity learning is giving better mathematics learning achievement than students with low learning creativity. (4) For each students level of creativity show that, cooperative learning model TGT modified AfL provides mathematics learning achievement better than cooperative learning model TGT and direct learning. TGT cooperative learning model provides better mathematics learning achievement than direct learning model.Keywords: cooperative learning, TGT modified AfL, TGT, creativity in learning, academic achievement.